Using game theory models to determine the profit maximization policies for PepsiCo and Coca Cola in Baghdad - جواد, لميعه باقر; سوادي, احمد عبد العزيز (Journal of Economics and Administrative Sciences, 2012)
(Use of models of game theory in determining the policies to maximize profits for the Pepsi Cola and Coca-Cola in the province of Baghdad)Due to the importance of the theory of games especially theories of oligopoly in the study of the reality of competition among companies or governments and others the researcher linked theories of oligopoly to Econometrics to include all the policies used by companies after these theories were based on price and quantity only the researcher applied these theories to data taken from Pepsi Cola and Coca-Cola In Baghdad Steps of the solution where stated for the models proposed and solutions where found to be balance points is for the two companies according to the principle of Nash.The theory of Cournot is based on the assumption that the total amount sold is fixed and is shared among the parties of monopoly (Companies). Aggregate supply is supposed to be determined and the price is set and supply meets demand. It also assumes that the relationship between price and quantity is linear: Quantity is inversely proportional to the price. the researcher has developed a proposed model for the expansion of the model to include all the policies used by oligopoly companies such as advertising and others.The model of von Staklberg is applied when there is a market leader and the rest of the companies are subsidiaries It takes the same relationship between price and quantity in the theory of Cournot that is the second company determines. the quantity that it wants to produce which will be restricted to the first company. This will be the first company the leader, and the second company to be its subsidiary. The researcher also to included all the policies used by oligopoly companies after linking the model to theories of econometrics.The Bertrand model depends mainly on determining the prices not quantities, as in the models of Cournot and von Staklberg. It is supposed that the price of competing companies in some way affects the price of a single company. The researcher also included all the policies used by oligopoly companies after the model was based on the price, quantity and sale price of the competing company only by linking the model to theories of econometrics.